2015
DOI: 10.1111/jai.12839
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships for six fish species in Iskenderun Bay (Eastern Mediterranean Sea coast of Turkey)

Abstract: Summary The length–weight relationships (LWRs) were estimated for six non‐indigenous fish species, namely, Apogon smithi (Kotthaus, 1970); Ostorhinchus fasciatus (White, 1790); Pomadasys stridens (Forsskål, 1775); Champsodon capensis Regan, 1908; Torquigener flavimaculosus Hardy & Randall, 1983; and Tylerius spinosissimus (Regan, 1908) from Iskenderun Bay, eastern Mediterranean Sea. Their length–weight relationship b values ranged from 2.902 to 3.501, and all regressions were found to be significant for all si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…In comparison with the studies performed in the natural distribution area; various parts of the western Indian Ocean, the maximum length values were apparently smaller in our study. In accordance with this, Edelist (2014) reported the maximum length of striped piggy as 14.5 cm from Israeli coasts and Ergüden et al (2015) as 17.7 cm from the Gulf of Iskenderun in the Mediterranean where is out of the native range. Along with the differences among the ecological properties of different study areas, this is probably because of that the striped piggy do not have a long history in our study area.…”
Section: Discussionsupporting
confidence: 61%
“…In comparison with the studies performed in the natural distribution area; various parts of the western Indian Ocean, the maximum length values were apparently smaller in our study. In accordance with this, Edelist (2014) reported the maximum length of striped piggy as 14.5 cm from Israeli coasts and Ergüden et al (2015) as 17.7 cm from the Gulf of Iskenderun in the Mediterranean where is out of the native range. Along with the differences among the ecological properties of different study areas, this is probably because of that the striped piggy do not have a long history in our study area.…”
Section: Discussionsupporting
confidence: 61%
“…The relationship between length and weight for this species indicates that growth shows positive allometry (b = 3.094) for combined sexes. Erguden et al (2015) reported negative growth (b=2.970) in their study conducted in Iskenderun Bay. Similarly, Bilge et al (2017) stated negative allometric growth (b=2.836) from the Mugla coast.…”
Section: Discussionmentioning
confidence: 91%
“…To date, length-weight relationship studies have been reported very scarcely for the pufferfish species (Erguden et al, 2015;Bilge et al, 2017;Ayas et al, 2019). Besides, LWRs and condition factors according to sexes for T. flavimaculosus have not been reported from the Eastern Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…This study reports the first record of this fish in the Syrian marine waters. The lack of scientific research in the study area [18], and fishermen ignorance to this species due to its small size (Max length 12.6 cm; [19] may had led this species not to be recorded previously in the area. This record fills the gap of O.fasciatus distribution along the eastern coast of the Mediterranean, between Iskenderun and Ashdod coasts.…”
Section: Discussionmentioning
confidence: 99%